Keragaman Genetik Inbrida Jagung QPM dan Normal Berbasis Marka Mikrosatelit dan Hubungannya dengan Penampilan Hibrida - Marcia B. Pabendon; M. Azrai; M. J. Mejaya; Sutrisno Sutrisno (Jurnal AgroBiogen, 2008)
Information on genetic divergence ofinbred lines and performance of the hybrids developed fromthe lines is a great value in maize hybrid program. A studywas conducted to evaluate genetic diversity of six QPM andfive normal maize inbred lines, to determine the relationshipbetween genetic distance based on SSR markers and thegrain yield of single cross hybrid, and to get informationpromising hybrid from the single cross of QPM hybrid.Twenty four polymorphic primers that covered the 10 maizechromosomes were used to fingerprint the lines, detectingin 94 alleles (average of 3.9 and a range of 2-6 alleles perlocus). Genetic divergences were determined using theJaccard’s similarity coefficient, and a dendrogram wasconstructed using the UPGMA. Cluster analysis divided theinbreds into two clusters that were confirmed by principalcoordinate analysis. Two promising QPM hybrids that arecrossed from different heterotic group were found. Theestimated value of simple correlations (r) of GDs with thegain yield of single cross hybrid was negatif (-0.07). There isa need to conduct more field trials to obtain more accuratecorrelations, particularly in a practical utility for predictingmaize hybrid performance for grain yield.